Seminoma clinical stage 1: patterns of care in Germany - Dieckmann, Klaus-Peter; Heinzelbecker, Julia (Urologia internationalis, 2016)
Introduction: International guidelines are ambivalent regarding the recommendations for the management of clinical stage 1 (CS1) seminoma. Patients and Methods: During 2008-2013, 1,050 patients with seminoma CS1 were prospectively registered with regard to assessing management modality (radiotherapy, carboplatin, surveillance). Associations with tumor size, rete testis invasion, age, year of diagnosis, type of institution, and geographic location were assessed. Results: Of the total number of patients, 49.3% received carboplatin 1 course, 8.5% carboplatin 2 courses, 35.9% surveillance, and 6.3% radiotherapy. In 2013, surveillance increased significantly to 57.9%. Treatment decisions were significantly associated with rete testis invasion and tumor size. Carboplatin was applied significantly more in office clinics than elsewhere. There is some regional variation regarding treatment preferences. Conclusions: The rising acceptance of surveillance mirrors international trends. The associations with prognostic factors demonstrate care givers to be compliant with contemporary guidelines. The association with the type of institution suggests non-oncological factors to be also relevant in decision making.